FILSAFAT PENDIDIKAN ISLAM - ., Mappasiara (Inspiratif Pendidikan, 2017)
The philosophy of Islamic education can be defined as a study of the various problems contained in the dynamics of the science of education based on the Qur'an and al-Hadith as primary sources and the opinions of experts as secondary sources. Islamic Education Philosophy became the concept of thinking about education based on the teachings of Islam about the nature of human ability to be nurtured and developed and guided into a Muslim man whose entire personality is imbued by Islamic teachings. By studying Islamic educational philosophy means entering the fundamental, systematic, logical, and universal arena of thought which derives from the teachings of Islam.